Draft Annual Plan 1994-95 Andhra Pradesh Volume-II (Sectoral Programmes) 9. Social Services - Planning Commission (Planning Commission, 1994)
An allocation of Rs.3392.00 lakhs was provided for implementation of welfare programmes for scheduled castes during 1993-94 and it is expected that the entire amount would be spent during the current year. For the year 1994-95 a sum of Rs.3392.00 lakhs is proposed.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh